Quality Evaluation of the Implementation of the Fe Tablet Program for Pregnant Women at Nasywa Clinic, Kisaran - Pratiwi, Debby; Anggriani, Ririn; Suryani, Elvi (PT Inovasi Pratama Internasional, 2023)
Globally, the prevalence of iron deficiency remains a significant concern among pregnant women, with an estimated 43.9% affected. The estimated prevalence of iron deficiency in pregnant women is 49.4% in Asia, 59.1% in Africa, 28.1% in the Americas, and 26.1% in Europe. The prevalence of substance deficiency in pregnant women in Indonesia remains relatively high, and deficiency plays a role in contributing to the high maternal and infant mortality rates observed in the country (Paridah, 2022). According to the Health Office profile (2020), the TTD coverage in pregnant women in North Sumatra Province in 2019 was 92.49%, representing a decline from the 2018 figure of 94.30%. The provincial coverage remains below the performance indicator and target for nutrition improvement activities in 2019, which is 95%. Furthermore, there was a reduction in the provision of TTD in four districts/cities. In Kisaran City, for instance, the coverage rate decreased from 93.30% in 2018 to 92.93% in 2019. This study employs a qualitative approach with a phenomenological design, with the aim of elucidating the phenomenon of implementing the Fe tablet program at the Nasywa Clinic in Kisaran in 2022. The study at Nasywa Clinic in Kisaran involved 50 pregnant women. It evaluated the Fe tablet supplementation program in 2022, revealing that health workers' collaboration in procuring and planning Fe tablets, along with midwives' distribution efforts, were crucial. However, the program's coverage did not meet targets, and pregnant women's compliance in taking Fe tablets was less than optimal.